Pengaruh Kualitas Makanan dan Kualitas Lingkungan Fisik terhadap Kepuasan Pelanggan PT Pioneerindo Gourmet International Tbk - Nathanael Surya Susanto; Richard Andrew (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
The objective of this research is to determine how food quality and physical environment quality influence each other. This population study employs a descriptive quantitative method. Utilizing the Google Form application to distribute the questionnaire online, we successfully collected responses from 104 respondents, all of whom met the criteria for the research sample. The purposive sampling method was used in this study, and the sample results were analyzed using Smart PLS 4.1 and the Partial Least Squares Structural Equation Model (PLS-SEM) method. The findings indicate that both exogenous factors—food quality and physical environment quality—positively and significantly affect customer satisfaction.